A green Y2O3:Eu3+ phosphor influenced by laser irradiation, incendiary agents, and annealing temperatures. (May 2019) - Zhou, Jun; Yang, Yuhua; Wang, Liu; Zhang, Xuehong; Wang, Lingling
Highlights: Different incendiary agents are used to prepare Y2 O3 :Eu 3+ (YOE) materials. The main peaks shift to 508 nm which is in the range of green light. Laser irradiation can influence the YOE photoluminescence properties. The smooth surface enhances charge transition and weakens charge quencher. Abstract: The Y2 O3 :Eu 3+ (YOE) materials were prepared by using different incendiary agents and annealed at different temperatures. In order to learn the influences by laser irradiation, incendiary agents, and annealing temperatures, the emission and excitation spectra of the as-synthesized YOE were measured. It is interesting that the highest emission peak has a big blue shift in our experiments, and the results imply the increase of photoluminescence (PL) intensity with the decrease of surface defects. Furthermore, the annealing temperature and laser radiation can affect the samples' emission and excitation spectra, higher annealing temperature is not always the best choice, it needs to be determined by different incendiary agents. The laser irradiation also influence the PL property of YOE sample greatly, which increases the PL intensity for all samples annealed at 800 °C and partly increases the PL intensity for the samples annealed at 600 °C.